Critical Analysis of The Standar Policy of The Learning Process in Schools/ Madrasah - Halida Umami; Salwa Cordova Syah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
In a learning, the standard of the learning process is needed to evaluate the learning process. In this study, the Researchers wants to explain about critical analysis of the standard policy of the learning process in schools. Things that become obstacles in a learning need to be overcome in order to be able to create a standard learning milieu starting from the standard of content, standards of the learning process, curriculum standards, and also standards in evaluating a learning process. This research is a literature reseacrh. Analysize some references from journals, books, magazines, and other sources of information. The result of this research is 1) Islamic religious education Learning standar process in school / Madrasah is the maximum standard of education related to the implementation of learning in an education to achieve graduate competence. 2) Components of islamic religious education Learning Process Standards include process planning, implementation of the learning process, learning outcomes, and supervision of the learning process. 3) Criticism of Islamic religious education learning process against the number of students one class exceeds the limits set in the standard process, the addition of effective out-of-hours lesson hours, with textbooks (LKS)